Methods for detection of Bacillus sp., B. cereus, and B. licheniformis in raw milk - Irena NĚMEČKOVÁ; Kateřina SOLICHOVÁ; Petr ROUBAL; Barbora UHROVÁ; Eva ŠVIRÁKOVÁ (Czech Journal of Food Sciences, 2011)
Totally 75 raw milk samples were analysed with the methods employing the media compared - MYPA, PEMBA, BrillianceTM Bacillus cereus agar, and HiCrome Bacillus agar. The reference method with MYPA seems to be the most suitable for dairy plants laboratories because there is only low risk of mistaken identity. However, the samples containing miscellaneous micro-flora should be heat-inactivated before plating. Both positive and negative strains (totally 132) were isolated. Twelve strains, which could cause problems in the evaluation of the plates, were selected and identified by phenotyping and by PCR methods for Bacillus sp., B. cereus, and B. licheniformis. The PCR methods differed in their selectivity within particular bacilli group, within genera Bacillus, and within raw milk microflora.